EMPOWERING MATURE WOMEN STUDENTS IN HIGHER EDUCATION - O'Brien, Mary; Whitmore, Elizabeth (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
In order to accommodate the large numbers of older women who are entering universities, institutions of higher education need to examine assumptions about how adults - particularly women students - learn. The distinctive life tasks of women reflect a particular need for self-fulfillment and gaining control over their lives. Inherent in the notion of control is empowerment. This study examines the concept of empowerment in the context of adult learning. A case study is used as an educational model which met the empowerment needs of a group of older women students. RÉSUMÉ Pour accueillir les nombreuses femmes d'un certain âge qui entrent à l'université, les établissements d'enseignement supérieur doivent analyser les hypothèses qui circulent sur le processus d'apprentissage des adultes, surtout des femmes. L'autonomie fonctionnelle distinctive des femmes traduit chez elles le besoin de s'épanouir et de prendre leur vie en main. Le concept de pouvoir est inhérent à la notion de contrôle. Cette étude examine le concept de pouvoir dans le cadre de l'éducation permanente. Une étude de cas sert de modèle éducatif répondant aux besoins de pouvoir d'un groupe d'étudiantes d'un certain âge.